Policy Implementation for Handling The Covid-19 Pandemic in DKI Jakarta Province - Mu’ammar Mu’ammar; Dyah Poespita Ernawati (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The purpose of writing this research is to identify and analyze the implementation of policies for handling the Covid-19 pandemic in the DKI Jakarta Province, and to analyze the work structure to overcome the inhibiting factors rather than the implementation of DKI Jakarta Provincial Government policies in the context of funding. This study was designed using 4 indicator dimensions, namely: communication, resources, disposition and bureaucratic structure. The method used is qualitative-descriptive which produces descriptive data in the form of speech or writing and behavior that can be observed from people (subjects), the techniques used to collect data are: observation, interviews, documents, and audio-visual material by testing the validity data through triangulation methods based on sources, methods, and theories. The informants in this study were Deputy Chairperson of the DKI Jakarta Provincial DPRD H. Misan Samsuri, Heri Kurniawan Head of BPK RI Representative for DKI Jakarta Province, Maria Margaretha Head of DKI Jakarta Provincial Social Service, Sigit Wijatmoko Plt. Head of DKI Jakarta Provincial Communication and Information Service, H. Nuri Thahir Community Leader, H. Jamal Hasrin Community Leader, and Syarif Darmawan Jakarta Youth Leader. Based on the results of this study, it can be concluded that overcoming the Covid-19 pandemic is an effort that requires the cooperation and seriousness of the government to mobilize all available resources at all costs. In addition to improving management, human resources and coordination, it is also important to put aside political factors first. Efforts to adjust the law must be maximized simultaneously with law enforcement efforts.